KONSENTRASI PASAR DAN POSISI TAWAR PETANI DALAM PEMASARAN TANDAN BUAH SEGAR (TBS) Market concentration and farmers bargaining power in the marketing of fresh fruit bunches (FFB) - Amin, Zaini (Societa: Jurnal Ilmu-Ilmu Agribisnis, 2014)
The research was conducted in Musi Rawas District. The purpose of research are to analyze: (1) con-centration and market structure in the marketing of fresh fruit bunches (FFB); and (2) the influence of marketing institutions in determining the price of FFB (bargaining power). The method used is literature study on estate Agen-cy of Musi Rawas and CPO plant operating in Musi Rawas. The data collected is the development of FFB and av-erage price of CPO during the last 10 years and the capacity of FFB absorption of each CPO plant.The results of this research showed that: (1) the structure of the FFB market tend oligopsonistic, the market concentration by HI = 1835.92; (2) the determination of FFB prices on the basis of the price of CPO and the age of the falm oil plant is not so effective in determining a market structure towards the perfect competition; (4) the results of multiple linear re-gression indicated that price is influanced by FFB prices at the level of middlemen and CPO prices simultanieously; (5) regression coefficient showed b1 and b2 <1, which means that markets tend oligopsonistic. Circumstances which farmers position as price taker.